Metacognitive Processes in Elementary Students’ Drawings: Proses Metakognitif dalam Gambar Siswa Sekolah Dasar - Yuliasanti, Imelda Selly; LINGGO WATI, TRI (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Metacognition, defined as thinking about thinking, plays an essential role in guiding students to plan, monitor, and evaluate their own learning processes. Specific background: In elementary education, students often struggle to control their learning strategies, particularly when faced with problem-solving tasks. Knowledge gap: Limited research has examined how young learners demonstrate metacognitive processes through creative outputs such as drawings. Aims: This study aimed to analyze how elementary school students apply metacognitive strategies when completing drawing tasks. Results: Two students were given three tasks with different themes—ideals, guided lines, and animals. Both students employed the stages of planning, monitoring, and evaluating, although with variations in depth according to their individual abilities. The drawings revealed how metacognitive processes shaped problem-solving approaches. Novelty: The study highlights the role of drawings as a medium to observe and understand students’ metacognitive processes. Implications: The findings suggest that incorporating metacognitive strategies in elementary education can support self-regulation, creativity, and more effective problem-solving. Highlights: Drawings reveal students’ metacognitive processes clearly. Planning, monitoring, and evaluating vary across individuals. Drawing tasks serve as effective tools for studying cognition. Keywords: Metacognition; Elementary School; Drawing; Problem-Solving; Self-Regulation